ANALISIS PERSPEKTIF ORANG TUA DALAM PENGAMBILAN KEPUTUSAN MEMILIH SEKOLAH : (Studi Kasus Pada Orang Tua Siswa SMK Buddhis Di Kabupaten Tangerang) - Hantoro Budiarto; Ida Ayu Gde Yadnyawati; Mettadewi Wong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Currently, Buddhist Vocational High Schools (SMK) have emerged in Indonesia. These schools are vocational high schools based on Buddhist teachings in their learning approach. However, 35%–40% of the students are non-Buddhists. This study aims to: 1) Analyze the underlying factors behind the decision-making of non- Buddhist parents in choosing Buddhist Vocational High Schools in Tangerang Regency, 2) Analyze the role of Buddhist values in the decision-making process of parents when selecting Buddhist Vocational High Schools in Tangerang Regency. This is a qualitative case study conducted at a Buddhist Vocational High School in Tangerang Regency, namely SMK Atisa Dipamkara. The subjects of this study are parents of non-Buddhist students enrolled in the Buddhist school. Data were collected using interview techniques. A total of eight (8) non-Buddhist parents were interviewed, consisting of one Muslim, four Christians, two Catholics, and one Hindu. Data analysis was carried out using the Miles, Huberman, and Sadana method. The results of the study are as follows: 1) The decision-making process of parents in choosing a Buddhist Vocational High School in Tangerang Regency is influenced by several factors, including the student’s interests and talents, school quality, distance, positive public perception, tolerance, school culture, Buddhist teachings, character education, positive values observed in Buddhist communities, and the desire to introduce diversity, 2) The Buddhist values that play a role in the parents’ decision-making in choosing a Buddhist Vocational High School in Tangerang Regency include inner peace, tolerance, meditation practices, loving- kindness, generosity (dāna), self-restraint, the law of karma, and respect for parents